Improving Urban Rail Efficiency: Analyzing Peak and Off-peak Capacity in the Jaipur Metro - manoj mittal; Chaturvedi, Anand Kishore (Journal of Railway Transportation and Technology, 2024)
This paper explores the optimization of train ratios for peak and off-peak hours in the Jaipur Metro. The study focuses on the impact of overtaking strategies, where fast trains overtake slow trains at specific locations. Six models were developed, analyzing various overtaking scenarios in terms of location and frequency. The models considered key factors like cycle time (time between consecutive trains), waiting time at stations, and passenger arrival rates during peak and non-peak hours. The analysis revealed that strategic overtaking can significantly reduce passenger waiting times, especially during peak hours. Additionally, it allows for more frequent train services without compromising travel times. Stations with high congestion can benefit from increased fast train ratios during peak times to manage passenger flow efficiently. These findings offer valuable insights for railway planners in the Jaipur Metro. The data-driven approach allows for optimizing train operations and improving passenger experience by reducing waiting times. Moreover, strategic overtaking enhances network efficiency by maximizing capacity utilization during peak hours. The paper concludes by highlighting the potential for further research, including exploring more complex modeling approaches and integrating the findings with existing scheduling software for implementation. By continuously optimizing train operations, the Jaipur Metro can provide a reliable, efficient, and comfortable public transportation system for its users.